The Effect of Managerial Ownership, Institutional Ownership, Independent Commissioners, and Firm Age on Debt Policy - Afiah Septia Rahmah; Angela Dirman (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2025)
The purpose of this study is to examine The Effect Of Managerial Ownership, Institutional Ownership, Independent Commissioners, And Firm Age on Debt Policy, both simultaneously and partially. This quantitative research with causal method takes the object of Retail Trade Subsector Companies on the Indonesia Stock Exchange for five years (2019-2023). The population amounted to 40 companies, and through purposive sampling technique, 15 companies is selected that met the criteria. The total sample analyzed is 75 data (15 companies multiplied by 5 years of observation). Secondary data from the company's financial or annual reports are processed using descriptive statistical analysis, classical assumption testing, hypothesis testing, and multiple linear regression analysis with the help of SPSS software version 25. The research findings reveal that Managerial Ownership and Institutional Ownership have a positive effect on Debt Policy. Meanwhile, Independent Commissioners and Firm Age have no effect on Debt Policy.